Multi-Trait Biochemical Features of Metarhizium Species and Their Activities That Stimulate the Growth of Tomato Plants - Siqueira, Ana Carolina Oliveira; Mascarin, Gabriel Moura; Gonçalves, Cassiara R. N. C. B.; Marcon, Joelma; Quecine, Maria Carolina; Figueira, Antonio; Delalibera, Ítalo (Frontiers in Sustainable Food Systems, 2020)
The interaction between Metarhizium spp., a genus of entomopathogenic fungi, and plant roots may provide a resourceful association to induce host plant growth and to control below- and above-ground pests and diseases. We conducted in vivo and in vitro bioassays using native Brazilian isolates of Metarhizium robertsii (ESALQ 1635), M. humberi (ESALQ 1638), and M. anisopliae (ESALQ 1669) to better understand the possible mechanisms related to plant growth promotion traits and colonization of the root system in the model pot-grown tomato (Solanum lycopersicum L.) miniature cultivar ‘Micro-Tom’. In vivo trials revealed that M. robertsii (ESALQ 1635) or M. humberi (ESALQ 1638) inoculated in tomato seedlings improved vegetative and reproductive traits. Inoculated plants with M. robertsii yielded taller plants, longer roots, and more shoot and root dry matters than M. humberi. The number of flowers, along with fresh and dry weight of fruits were significantly increased by M. robertsii in relation to M. humberi-inoculated or uninoculated control plants. M. robertsii and M. humberi were able to endophytically colonize all tomato tissues by up to 30 days after inoculation. Plants inoculated with either M. robertsii or M. humberi increased auxin-induced GUS expression in the roots at 10 and 30 days after inoculation, confirming that Metarhizium induces auxin-regulated gene expression. We also explored their production of key compounds including enzymes, hormones, and metabolites involved in plant growth promotion. The three fungal species grown with or without exogenous tryptophan were able to produce indole-3-acetic acid (IAA) at different titers. All Metarhizium isolates produced phosphatases, phytases, siderophores and chitinases. Of particular importance, the M. robertsii and M. humberi isolates exhibited similar in vitro biochemical profiles, whereas M. anisopliae and Trichoderma harzianum isolates, demonstrated distinct traits from the others. Taken together, we argue that the M. robertsii isolate is more prone than the M. humberi isolate to endophytically colonize tomato plants resulting in improved growth. However, M. humberi (ESALQ 1638) yielded slightly better production of some metabolites in vitro. Thus, we propose that both isolates of M. robertsii and M. humberi could be explored together, as they possess complimentary properties, for use as plant growth promoters.